Analisis Vegetasi di Lahan Bekas Penambangan Timah Desa Rebo, Kabupaten Bangka - Lestari, Tri; Abdi, Zainal; Widodo, Joko; Yohanes, Yohanes (ENVIAGRO, 2008)
The Vegetation Analize of Ex-Tin Mining Land  in Rebo Village, Bangka This research was conducted by observing a number of interconnected ecological variables with spreading of vegetations on ex-tin mining land, located in Rebo Village, Bangka Regency from May to july 2008.   Vegetation analysis can be utilized to determine types of dominant and pioneer plant  spesies being able to grow in  ex-tin mining land for revegetation.  This analysis indicates that the following pioneer or dominant plant spesies common in the studued are of ex-tin mining land, these are among mengkirai (Commersonia sp), mentenuk (Trema orientalis L), kedebik (Melastoma malabathricum L) and leban (Vitex pinnata L).  These plant spesies were the common one whitin the category of seedling, sapling, pole and tree respectively.  Keywords :Ex-tin mining land,  Revegetation of pioneer plant.